Anemia in pregnancy in Western Jamaica - Wright S; Earland D; Sakhuja S; Junkins A; Franklin S; Padilla L; Aung M; Jolly PE (Dove Medical Press, 2017)
Saidah Wright,1 Dominique Earland,1 Swati Sakhuja,1 Anna Junkins,1 Sarah Franklin,1 Luz Padilla,1 Maung Aung,2 Pauline E Jolly1 1Department of Epidemiology, School of Public Health, University of Alabama at Birmingham, Birmingham, AL, USA; 2Western Region Health Authority, Cornwall Regional Hospital, Ministry of Health, Montego Bay, Jamaica Background: Anemia is one of the most prevalent problems in pregnancy. In 2011, 29.9% of all pregnant women in Jamaica were diagnosed with anemia.Objective: The objective of this study was to determine the prevalence and predictors of anemia in pregnancy in Western Jamaica.Methods: A cross-sectional study was conducted among 293 mothers attending post-natal clinics in Western Jamaica. A questionnaire was administered to the mothers, and an abstraction form was used to collect clinical data from the mothers’ records.Results: The prevalence of anemia among the women was 37.6%. Younger mothers (aged 18–24 years) were more likely to be anemic compared to those ≥35 years (odds ratio [OR]: 3.44, 95% CI: 1.07–11.06). Mothers who reported not always washing their hands after using the toilet were almost 10 times more likely to be anemic (OR: 9.7, 95% CI: 1.72–54.78) compared to those who reported always washing their hands. Mothers who attended a public facility for antenatal care were 2.3 times more likely to be anemic (OR: 2.31, 95% CI: 1.03–5.18) compared to those who obtained care at a private facility, and mothers who reported being told that they were anemic by a health care provider (HCP) were almost six times more likely to be anemic compared with those who were not told (OR: 5.58, 95% CI: 1.73–17.93).Conclusion: The results of the study indicate that early identification and treatment of anemia, especially among younger pregnant women, should be a priority. HCP should ensure that women understand the need to be cured of their anemia and to adhere to preventive hygienic practices. Keywords: predictors of anemia, hygienic practices, ANC facilities, Healthcare Providers’ communication